The effect of testosterone on ovulatory function in transmasculine individuals - Taub, Rebecca L.; Ellis, Simon Adriane; Neal-Perry, Genevieve; Magaret, Amalia S.; Prager, Sarah W.; Micks, Elizabeth A. (American journal of obstetrics and gynecology, 2020)
An estimated 1.4 million persons in the United States identify as transgender or nonbinary, signifying that their gender identity does not correspond with their assigned sex at birth. Individuals assigned female at birth may seek gender-affirming hormone therapy with testosterone. No studies have directly examined ovulatory function in transmasculine individuals using injectable testosterone. Our primary objective was to determine the effect of testosterone on ovulatory suppression in transmasculine individuals. Secondary objectives were to determine predictors of ovulation in transmasculine individuals on testosterone, and to assess the effect of testosterone on antimüllerian hormone. This prospective observational study recruited participants from a community clinic that provides gender-affirming hormone therapy. Enrolled individuals were assigned female at birth and were currently using or seeking to initiate masculinizing therapy with injectable testosterone esters (transmasculine individuals). Over a 12-week study period, participants collected daily urine samples for pregnanediol-3-glucoronide testing and completed daily electronic bleeding diaries. We assessed monthly serum mid-dosing interval testosterone, estradiol and sex hormone binding globulin, and antimüllerian hormone values at baseline and study end. Ovulation was defined as pregnanediol-3-glucoronide greater than 5 μg/mL for 3 consecutive days. The primary outcome was the proportion of participants who ovulated during the study period. We examined predictors of ovulation such as age, length of time on testosterone, serum testosterone levels, body mass index, and bleeding pattern. From July to November 2018, we enrolled 32 individuals; 20 completed the study (14 continuing testosterone users, 6 new users). Median age was 23 years (range 18−37 years). Bleeding or spotting during the study period was noted by 41% of participants (13/32). Among continuing users, median testosterone therapy duration was 11 months (range 1−60 months). A single ovulation was observed out of a total of 61 combined months of testosterone use; however, several transient rises in pregnanediol-3-glucoronide followed by bleeding episodes were suggestive of 7 dysfunctional ovulatory cycles among 7 individuals. There was no difference in antimüllerian hormone from baseline to 12 weeks between participants initiating testosterone and continuing users of testosterone. We did not have the power to examine our intended predictors given the low numbers of ovulatory events, but found that longer time on testosterone and presence of vaginal bleeding over 12 weeks were associated with transient rises in pregnanediol-3-glucoronide. This study suggests that testosterone rapidly induces hypothalamic−pituitary−gonadal suppression, resulting in anovulation in a proportion of new users. Importantly, these data also suggest that some long-term testosterone users break through the hormonal suppression and experience an ovulatory event, thereby raising concerns pertaining to the need for contraception in transmasculine individuals engaged in sexual intercourse with sperm-producing partners. Given the small number of overall participants, this work is hypothesis generating. Larger studies are needed to confirm and to clarify these findings.